Hancurnya Eksotika Interaksi Masyarakat Dengan Sungai di Kelurahan Kuin Utara Kota Banjarmasin - Fitria, Qolbiatul; Hamid, Ismar (Prodi Sosiologi FISIP ULM, 2024)
The life of a society always adapts to the characteristics of its environment and its changes, and social changes in a society also affect changes in environmental conditions. This research aims to describe the metabolic relationship between the community and the river and analyse the form of interaction rift due to social change and river ecosystem degradation. This research uses qualitative methods, with the type of phenomenological research. The research was conducted in North Kuin Village, Banjarmasin City. Data were collected using observation, in-depth interviews and documentation. Data were analysed using the Miles & Huberman interactive model. The results showed that the community's interaction with the river in the past was intertwined in a strong attachment. The community depends on the resources and services of the river environment to sustain their daily lives. This is sourced from the condition of the Kuin River ecosystem which is still balanced and has not experienced high pollution. However, the condition of the river ecosystem then experienced significant degradation. So that the interaction between the community and the river has cracked or can no longer support each other. Ironically, the degradation of the Kuin river ecosystem is dominantly caused by various community activities from upstream to downstream of the Kuin river. Finally, alienation between the community and the river is created, exploitation that continues to be carried out by humans results in both (humans and rivers) exploiting and being exploited. Behavioural changes are needed in the community in interacting with the river, as well as action programs to restore the condition of the Kuin river ecosystem, to create a sustainable river community life.